2022
DOI: 10.1186/s40981-022-00556-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of remimazolam in living donor liver transplantation: a case report

Abstract: Background Remimazolam is an intravenous ultra-short-acting benzodiazepine with the benefit of hemodynamic stability, including blood pressure and pulse rate. We report a case in which remimazolam was used in living donor liver transplantation with stable hemodynamics. Case presentation A 19-year-old woman underwent living donor liver transplantation due to end-stage liver disease, which is associated with a hyperdynamic state and hemodynamic insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Onoda et al showed that remimazolam had been used in anesthesia management of liver cirrhosis patients [12] and this was consistent with the present study. Matsumoto et al [13] and Kawasaki et al [14] reported that remimazolam could be used in liver transplantation with small fluctuation of perioperative blood flow. The present study showed that propofol combined with remimazolam toluene sulfonate could be used in liver transplantation, reduce the dose of propofol, decrease the incidence of intraoperative hypotension, reduce the use of vasoactive drugs and provide stable hemodynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Onoda et al showed that remimazolam had been used in anesthesia management of liver cirrhosis patients [12] and this was consistent with the present study. Matsumoto et al [13] and Kawasaki et al [14] reported that remimazolam could be used in liver transplantation with small fluctuation of perioperative blood flow. The present study showed that propofol combined with remimazolam toluene sulfonate could be used in liver transplantation, reduce the dose of propofol, decrease the incidence of intraoperative hypotension, reduce the use of vasoactive drugs and provide stable hemodynamics.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by rapid onset and quick recovery, with fewer cardiac side effects during general anesthesia, such as hypotension or bradycardia (3,8). Some reports have demonstrated that remimazolam maintained stable hemodynamics during anesthetic management in patients with expected hemodynamic instability (9,10). Tracheal extubation under deep anesthesia leads to less airway stimulation by an endotracheal tube than extubation while the patient is awake and reduces the incidence of coughing, bucking, and hemodynamic changes due to tracheal tube movement (11).…”
Section: Discussionmentioning
confidence: 99%
“…While the loss of consciousness was faster after propofol versus remimazolam induction (46 versus 66 s), blood pressure was significantly lower after propofol induction. 103 Japan VATS Anaesthesia 1 100% Anaphylaxis Hong 9 Korea Arthroscopy Anaesthesia 1 0% Horikoshi 10 Japan Laparoscopy Anaesthesia 1 100% Delayed emergence Huang 11 China LMA insertion Anaesthesia NA 0% Hwang 12 Korea Teratoma resection Anaesthesia 2 0% Kawasaki 13 Japan Liver transplantation Anaesthesia 1 0% Kida 14 Japan CABG Anaesthesia 1 100% Tolerance Kim 107 Korea All kinds Anaesthesia 5 100% Anaphylactoid shock Kim 15 Korea THA Anaesthesia 1 100% Psychogenic coma Kim 16 Korea Laparotomy Anaesthesia 1 0% Kitaura 17 Japan TMVR Anaesthesia 1 0% Koh 18 Japan Spine Anaesthesia 1 100% Heart failure Lee 19 Korea RALP Anaesthesia 1 0% Liu 110 China RALP Anaesthesia 1 100% Precipitation Matsumoto 20 Japan Liver transplantation Anaesthesia 1 0% Matsuo 111 Japan Orthopaedic Anaesthesia 1 100% Precipitation Nakayama 21 Japan Minor orthopaedic Anaesthesia 2 0% Onoda 22 Japan Laparoscopy Anaesthesia 1 0% Saito 23 Japan Cardiac Anaesthesia 1 100% Hypotension Sasaki 112 Japan Dental Anaesthesia 1 100% Precipitation Sato 24 Japan Trepanation Anaesthesia 1 0% Sato 25 Japan Cardiac Anaesthesia 1 100% Hypertension Singal 102 USA Endoscopy Anaesthesia 1 100% Delayed emergence Suzuki 26 Japan ENT Anaesthesia 1 100% Delayed emergence Takemori 27 Japan RALP Anaesthesia 1 100% Delayed emergence Tsurumi 104 Japan Minor orthopaedic Anaesthesia 1 100% Anaphylaxis Uchida 28 Japan ENT Anaesthesia 1 100% Delayed emergence Uchida 29 Japan TEVAR Anaesthesia 1 100% Delayed emergence Uchida 106 Japan Skin graft; laparoscopy Anaesthesia 2 100% Anaphylaxis Yamada 30 Japan Neurosurgery Anaesthesia 3 0% Yamadori 31 Japan Laparotomy Anaesthesia 1 0% Yamamoto …”
Section: Discussionmentioning
confidence: 99%